VIOLENCE AGAINST WOMEN IN MASS MEDIA FRAMEWORK - Sari, Mungky Diana; Mahestu, Gayes; Soraya, Kiky (SEEIJ (Social Economics and Ecology International Journal), 2017)
This study aims to see how far media positioned women, especially in their news frames. The focus of this research will be more about seeing how are violence against women cases in the mass media framework, especially online media. The selection of online media in this research is because the access of information provided by online media is much wider and easier in comparison with other media, especially mainstream mass media like newspaper. The focus of this study is on violence against women which occurred on a high school student in Bengkulu that resulted on her die. The method used in this study is the framing method of Robert Entman, by looking at the articles on Detik.com and Tribunews.com in May 2016. The results of this study indicate that Detik.com put women as objects, while Tribunews.com a little more put women as subjects, though not yet fully in the entity as a woman.